Hubungan Pengetahuan, Sikap dan Ketersediaan Sarana Prasarana dengan Perilaku Pengolahan Limbah Medis oleh Petugas Kebersihan - Tri Puji Laksono, Galih; Sari, Agustina (Journal of Public Health Education, 2021)
Introduction: The development of health service facilities is currently growing rapidly, but on the other hand, the waste produced is a threat in itself to environmental sustainability. Therefore, the health service unit has the obligation and responsibility to manage the waste produced, including in the hospital. Objectives: The research objective was to determine the relationship between knowledge, attitudes and infrastructure towards the behavior of medical waste treatment by cleaners in the Thousand Islands Regional Hospital in 2020. Method: The quantitative research method used a cross sectional design. The population of this study were all employees of the Seribu Kepuluan Regional General Hospital. The sampling technique used was purposive sampling with a total sample size of 106 people. The data used are primary data through distributing questionnaires and secondary data from books and literature. Data analysis was performed by univariate and bivariate with the chi- square test. Result: The results showed the relationship between knowledge with (p-value = 0,000 and OR = 43,333), attitude with (p-value = 0,000 and OR = 12,692), and infrastructure (p-value = 0,000 and OR = 25,143) on waste management behavior. medical by janitor. There is a relationship between knowledge, attitudes, and facilities and the behavior of medical waste management by cleaning workers. Conclution: It is hoped that the Seribu Islands Regional General Hospital will provide training, and provide complete facilities and infrastructure in medical waste management in order to increase the knowledge of hospital staff and maximize medical waste management.